Effects of transportation time after extraction on the magnetic cryopreservation of pulp cells of rat dental pulp - Mao-Suan Huang; Wei-Jen Chang; Haw-Ming Huang; Yen-Chuang Lin; Yen-Hua Huang; Jen-Chang Yang; Sheng-Yang Lee (Elsevier, 2011)
Background/purpose: The aim of this study was to examine the effects of the time period between tooth extraction and the freezing procedure on pulp cells in frozen intact teeth of rats. Material and methods: In total, 120 incisors from 30 rats were extracted and kept in transportation solution for 0 hour, 12 hours, and 24 hours. The tested teeth were divided into 2 experimental groups, where the extracted incisors were first frozen in a magnetic-programmed freezer (PF) or a traditional −20°C freezer (TF). The tested teeth were then stored at −150°C for 7 days. Incisors extracted from the opposite side of the same rat were treated as the non-frozen control. After thawing, the pulp was extracted and dissected. Hematoxylin and eosin staining was performed to observe the cell distributions. Cell densities in the odontoblast region and cell-rich zone were calculated using an optical microscope. Results: When samples were immediately frozen after extraction, the cell density of odontoblastic cells was higher in the PF group compared with analogs which were frozen in the −20°C freezer (P < 0.05). In the cell-rich zone, cell densities of the PF group were significantly higher (P < 0.05) than those of the TF group although the pulp cells had been stored in transportation solution for 24 hours before being frozen. Conclusions: The freezing technique used in this animal study provided positive effects on pulp cell storage. In addition, the storage time before the freezing procedure is an important issue for cryopreserving pulp cells in intact teeth.